Поняття та структура об'єкта злочинів у сфері службової діяльності - Михайленко, Дмитро Григорович; Михайленко, Дмитрий Григорьевич; Mykhailenko, Dmytro (Одеса : Юрид. л-ра, 2012)
The article studies the notion and the structure of a target of crimes stipulated by Chapter XVII of the Criminal Code as a group of protected legal relationship. The idea of distinction between criminal protection of service in public and private spheres is explained. The differentiation by target of crimes in the sphere of official activity and crimes against the administrative procedures is made.
Михайленко Д. Г. Поняття та структура об'єкта злочинів у сфері службової діяльності / Д. Г. Михайленко // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 521-531.
Keywords: суспільні відносини; об'єкт злочину; злочини у сфері службової діяльності; злочини проти порядку управління; общественные отношения; объект преступления; преступления в сфере служебной деятельности; преступления против порядка управления; social relations; target of a crime; crimes in the sphere of official activity; crimes against administrative procedures